Bit error rate modelling for asynchronous DS-CDMA system with Nyquist pulse shaping - Ng, Kiat Wah. (2008)
One of the main objectives of this research is to study the effects of pulse-shaping filters on the bit error rate (BER) performance of asynchronous Direct Sequence Code Division Multiple Access (DS-CDMA) systems operating in multipath fading channels. Closed-form analytical BER formulas for asynchronous DS-CDMA system using BPSK transmission and coherent RAKE reception are derived. The BER formulas are versatile as they contain flexible parameters to model the effects of practical system settings such as number of users, number of fading paths, Nakagami m-parameter per fading path, spreading ratio, filter roll-off factor, voice activity factor, cell loading factor etc. The derived formulas are verified accurate by means of Monte Carlo simulations performed using MATLAB programming.